Spatio-temporal variability of streamflow in major and medium rivers of Nepal - Aryal, Anil; Shrestha, M.; Aryal, S.; Upadhyay, S.; Maharjan, M. (Elsevier, 2023)
Study region: We selected six (three on each) major and medium river basins of Nepal as a study domain for the analysis. The study areas were so selected that they represent the river basins across the country from East (Kankai basin) to West (Karnali basin). Study focus: This study focuses on the long-term hydrologic alteration in the river flow of Nepal's medium and major rivers of different river basins. The overarching objective of the study is to evaluate the spatio-temporal change in flow magnitude, duration, frequency, timing, and rate of change in the major and medium rivers in Nepal. With continuity in the development activities, it is imperative to analyze the potential impact of human activities in the hydrologic regimes. For this, we used a set of 33 indicators from the indicator of hydrologic alteration (IHA) developed by The Nature Conservancy for the pre and post-impact period. The pre and post-impact period is defined here as the time before and after which the substantial alteration occurred, possibly due to multiple reasons. The pre and post impact periods were determined using the Pettitt statistical test carried out at the most downstream of the hydrological gauge station of each river basin. Further, the trends in the annual flow were estimated using the Mann-Kendall test, and the slope of the trend was estimated using Sen’s slope. New hydrological insights for the region: The results showed that in the post-impact period, the mean annual discharge in major and medium rivers of Nepal was found to decrease by 5.86% and 7.94%, respectively. Except for the West Rapti River (−14.3%), the hydrologic change of 1-day maximum flow is observed to have increased in the medium rivers and decreased in the major rivers. Moreover, except for the Kankai River (+14.29%), the hydrologic change of 1-day minimum flow is observed to be reduced in both the major and medium rivers. In major rivers, the overall degree of alteration ranges from 28.7% to 38.0%, which resembles the low to mid variability range. Similarly, the result of the hydrologic alteration showed that for the medium rivers, the overall degree of alteration varied from 35.8% to 46.7%, representing the medium range of variability. This suggests that the river systems undergoing moderate hydrologic alteration have experienced moderate alteration. These rivers might be capable of sustaining a healthy ecosystem, however, could be more susceptible to other stressors like drought.